Analysis of the IFN-γ-induced signal transduction pathway in fetal rejection - Irene Athanassakis (Mediators of Inflammation)
The placenta, one of the most important fetal tissues during gestation, ensures nutrition, development and protection of the fetus. Although placenta lacks expression of class II MHC antigens, they can be induced either by interferon-gamma (IFN-γ) on the spongiotrophoblast zone, or by 5-azacytidine (5-azaC) on the labyrinthine trophoblast zone, two agents actively participating in a plethora of immunological and inflammatory reactions. This induction is correlated with fetal abortion and fetal developmental abnormalities. In this work the in vitro and in vivo signal transduction pathways followed by IFN-γ or 5-azaC to induce class H antigen expression on placental cells by using specific pathway inhibitors has been studied. It is shown that at least three intracellular pathways are implicated in the Ia induction, p21ras is the first protein activated by the two agents while further signalling requires Ca2+ mobilization and PKC activations. When the in vitro results are transferred to live animals using the same inducing agents and pathway inhibitors, it is found that theophylline (Ca2+/CaM inhibitor) and anti-p21ras are the most potent suppressors of the IFN-γ- and 5-azaC-induced side effects during pregnancy. The data presented here point to novel directions not only as to the intracellular signalling, but also to the use of pathway inhibitors in vivo to treat aberrant antigen expression associated with fetal loss.